Analysis of organizational resilience in times of Covid-19: A bibliometric overview - Pérez Martínez, Norma Guadalupe; Vega Esparza, Reina Margarita; López López, Yenia Yahaira Guadalupe (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. We examined bibliometrically research on organizational resilience at the time of COVID-19. Design/Methodology/Approach. The bibliometric methodology was used after combining performance with scientific mapping. The SCIMAT software was used, through which areas obtained diagrams and issues. Publications related to organizational resilience and COVID-19 in Scopus during 2020-2021 were considered. Results/Discussion. 338 publications from 77 countries were processed. The authors of the most cited articles were: Filimonau, V, Prayag, G., Duchek, S., Heath, C., Sommerfield, A., von Unogern-Sternberg, B.S., Derqui, B., and Matute, J. The most productive countries were: the United States, the United Kingdom, China, Italy, Germany, and Australia. The main area of knowledge was business, management and accounting, and social sciences. The topic that had the most significant number of publications in 2020 was Organizational-Performance (44), continuing with Management-Models (31), which was encountered in quadrant 4 (Q4). Concerning 2021, the topic with the highest number of publications was Leadership-Management (54). Conclusions. Topics and sub-themes of interest to the business field have been developed. That can be taken as a basis for future research since Covid-19 has impacted both people and public and private organizations.